Cognitive-motor dual task induces strategic kinematic adjustments with increased toe-obstacle clearance for older adults during obstacle crossing - Shiuan-Huei Lu; Yi-Chun Kuan; Kuan-Wen Wu; Ting-Ming Wang; Tung-Wu Lu (PLoS ONE, 2025)
Background and objectives Falls among older adults, especially during obstacle crossing, lead to severe outcomes like fractures and higher healthcare costs due to declining cognitive and motor functions. The study aimed to quantify the kinematic adjustments at individual joints and end-points of the pelvis-leg apparatus in older adults during cognitive-motor dual task involved crossing obstacles of varying heights while performing serial subtraction. Methods Sixteen healthy older adults each walked and crossed obstacle of three varying heights with leading and trailing limb under single-task and dual-task conditions. Toe-obstacle clearances and pelvic and lower limb angular motions were calculated. Two-way analyses of variance were conducted to study within-subject (task and height) effects on the variables. Results Older adults showed significantly reduced crossing speed and increased leading and trailing toe-obstacle clearances. During dual-task obstacle crossing, there were increased pelvic anterior tilt, swing hip abduction and knee flexion, but decreased stance hip adduction at leading-limb crossing, compared to single-task (p < 0.05). There were increased in pelvic posterior tilt and swing knee flexion, but decreased pelvic upward list, stance hip adduction and stance knee flexion during dual-task obstacle crossing at trailing-limb crossing (p < 0.05). Discussion and implications The study found healthy older adults showed reduced crossing speed and adapting behaviour, with distinct kinematic changes at the pelvis, hip, and knee joints, leading to increased toe-obstacle clearances. While this may affect balance adversely. To mitigate fall risks, older adults should consider balance training and avoid distractions like phone use during obstacle crossing. Future studies should explore unexpected obstacles and its effects on at-risk populations.